STAKEHOLDERS' ISSUES AND ANALYSIS OF CARBON CAPTURE AND STORAGE (CCS) TECHNOLOGY ADOPTION IN MALAYSIA - KEE, TAN SIOK (2016)
The constantly increased of atmospheric carbon dioxide (C02) level has implicated severe climate change which in turn attracts widespread global concerns. The main sources of CO2 emissions are combustion from coal-power generation, natural gas production, automobiles and agriculture to name a few. Carbon capture and storage (CCS) technology are known to be one of the key technologies that can be implemented to mitigate climate change